Nanoparticle-induced morphological transformation in block copolymer-based nanocomposites. Issue 24 (8th June 2022) - Ji, Wenhai; Huang, Zhongyuan; Kentzinger, Emmanuel; Rücker, Ulrich; Brückel, Thomas; Xiao, Yinguo
Abstract : Using AFM and X-ray scattering technique (GTSAXS), the morphological transformation of supramolecular nanocomposite thin films induced by incorporated nanoparticles is revealed as a function of the nanoparticle concentration. Abstract : By controlling the chemical composition and the spatial organization of nanoparticles, hybrid nanocomposites incorporating ordered arrangements of nanoparticles could be endowed with exotic physical and chemical properties to fulfill demands in advanced electronics or energy-harvesting devices. However, a simple method to fabricate hybrid nanocomposites with precise control of nanoparticle distribution is still challenging. We demonstrate that block copolymer-based nanocomposites containing well-ordered nanoparticles with various morphologies can be readily obtained by adjusting the nanoparticle concentration. Moreover, the structural evolution of nanocomposite thin films as a function of nanoparticle loading is unveiled using grazing-incidence transmission small-angle X-ray scattering and atomic force microscopy. The morphological transformation proceeds through a phase transition from perforated lamellae to in-plane cylinder layout, followed by structural changes. The successful achievement of a variety of morphologies represents an effective and straightforward approach to producing functional hybrid nanocomposites for potential applications in various functional devices.